Antidiabetic properties of beer enriched with Baccharis dracunculifolia (Research, Society and Development, 2022)
Objective: The objective of the present study was to verify the metabolic responses of a beer with Baccharis dracunculifolia added in diabetic patients. Methodology: Participants in the study were 06 volunteer individuals diagnosed with type 2 diabetes mellitus. Biochemical analysis and physical evaluation took place before and after 30 days of treatment with beer with B. dracunculifolia. Results: After receiving the beer treatment with B. dracunculifolia, the patients showed a decrease in creatinine levels (23%). Alkaline phosphatase also had a reduction (23%) in its production. In addition, a reduction in the lipid profile for LDL (15%) was observed. Still, the levels of TGO and TGP had a significant reduction of 42% and 25%, respectively. Blood glucose levels after treatment reduced margins by 22%. Conclusion: In conclusion, beer enriched with B. dracunculifolia offers promising therapeutic value in preventing diabetes and dyslipidemic profile.